Strategy of the Sociology Education Study Program Student Executive Body (Bemp) to Achieve Work Programs at Jakarta State University - Dian Jesica Simanjuntak; Elin Nur Fadila; Naia Regitha (Formosa Journal of Applied Sciences, 2023)
This research was influenced by the important role of BEMP as a student organization that plays an active role in developing and realizing programs that are beneficial to students. The method used in this study was a qualitative method with a descriptive approach used with 4 (four) informants consisting of the general chairman and 3 division heads. The purpose of this research is to gain a deep understanding of the strategies that are effectively used by BEM in achieving work programs. The results of the study show that the strategies used in BEMP Sociology Education include: member participation, detailed and realistic plans, and time management. With this research it is hoped that it will become a source of information and reference for students and lecturers as a guide or description of strategies that can be carried out by student organizations.